2014
DOI: 10.1111/cei.12324
|View full text |Cite
|
Sign up to set email alerts
|

A novel luminescence-based method for the detection of functionally active antibodies to muscarinic acetylcholine receptors of the M3 type (mAchR3) in patients' sera

Abstract: In different bioassays, functional antibodies reacting with the human muscarinic acetylcholine receptor M3(mAchR3) have been detected in sera from patients with Sjögren's syndrome (SS), and there is strong evidence that those antibodies may have pathogenetic relevance. However, depending on the method of detection, their prevalence varied. Furthermore, those bioassays are difficult to standardize. We report on the development and optimization of a novel test system based on a luminometric method to determine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Second, two independent studies identified specific autoantibodies against mAChR3 in PBC patients . It might be of interest to add that inhibitory mAChR3 autoantibodies have also been described in patients with Sjögren's syndrome and systemic sclerosis leading to impaired mAChR3‐mediated signaling in vitro . Most important, genetic loss of mAChR3 aggravated bile duct destruction in a well‐established mouse model of chronic biliary inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, two independent studies identified specific autoantibodies against mAChR3 in PBC patients . It might be of interest to add that inhibitory mAChR3 autoantibodies have also been described in patients with Sjögren's syndrome and systemic sclerosis leading to impaired mAChR3‐mediated signaling in vitro . Most important, genetic loss of mAChR3 aggravated bile duct destruction in a well‐established mouse model of chronic biliary inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 It might be of interest to add that inhibitory mAChR3 autoantibodies have also CHRM3 polymorphisms in PBC and PSC 327 Hepatology Research 2020; 50: 321-329 been described in patients with Sjögren's syndrome and systemic sclerosis leading to impaired mAChR3mediated signaling in vitro. 20,21 Most important, genetic loss of mAChR3 aggravated bile duct destruction in a well-established mouse model of chronic biliary inflammation. 22 From that, we hypothesize that impaired mAChR3-mediated signaling might affect the so-called biliary bicarbonate umbrella, which has been postulated to protect cholangiocytes from aggressive bile acids in the bile ducts.…”
Section: Discussionmentioning
confidence: 99%
“…CHO cells (CHO-K1) stably transfected with a calcium-sensitive bioluminescent fusion protein consisting of aequorin and green fluorescent protein (GFP) were kindly provided by Dr. Stefan Offermanns (Max-Planck-Institute for Heart and Lung Research, Bad Nauheim, Germany) and were cultured as described ( 30 ). These cells are indicated as CHO/G5A.…”
Section: Methodsmentioning
confidence: 99%
“…We have, therefore, recently established a novel test system for the demonstration of functional anti-mAChR3-antibodies in patients' sera. It is based on the determination of downstream signaling of mAChR3 using Chinese hamster ovarian (CHO) cells transfected with plasmids encoding mAChR3 and a green fluorescence protein (GFP)/aequorin fusion protein ( 30 ). Thus, activation of G protein-coupled receptors (GPCR) leads to an opening of Ca 2+ channels in the endoplasmic reticulum; the resulting efflux of Ca 2+ can be visualized with a luminometric assay.…”
Section: Introductionmentioning
confidence: 99%
“…A bioassay was developed to screen for functional antibodies against muscarinic acetylcholine receptor M3 in sera from patients with Sjogren′s syndrome . Rises in Ca 2+ were detected in response to carbachol by a GFP‐Aeq fusion expressed in CHO cells, and antibodies in patients’ sera inhibited the activation of the receptor.…”
Section: Applications Of Fp–photoprotein Fusionsmentioning
confidence: 99%